2015
DOI: 10.1037/pspp0000017
|View full text |Cite
|
Sign up to set email alerts
|

The dispositional basis of attitudes: A replication and extension of Hepler and Albarracín (2013).

Abstract: As a departure from traditional situational perspectives, researchers have given increased attention to the dispositional basis of attitudes. Recently, Hepler and Albarracín (2013) introduced a construct that they called "dispositional attitude" and provided validity evidence for a new scale--the Dispositional Attitude Measure (DAM). Although the DAM was introduced as a "new" approach for assessing the dispositional component of attitudes, there is considerable conceptual similarity between it and the Neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
1
17
0
1
Order By: Relevance
“…Further, dispositional attitude certainty predicted certainty in a newly formed attitude. Indeed, the DAS and DAS-C each uniquely positively predicted their corresponding measure (i.e., attitudes and attitude certainty, respectively) toward a novel object, providing a close replication of Hepler and Albarracín (2013; see also Eschleman et al, 2015), and extending their work to predicting certainty in a novel attitude. In Study 4, we seek to further explore dispositional attitude certainty by examining whether it predicts important attitudinally relevant outcomes.…”
Section: Discussionmentioning
confidence: 71%
“…Further, dispositional attitude certainty predicted certainty in a newly formed attitude. Indeed, the DAS and DAS-C each uniquely positively predicted their corresponding measure (i.e., attitudes and attitude certainty, respectively) toward a novel object, providing a close replication of Hepler and Albarracín (2013; see also Eschleman et al, 2015), and extending their work to predicting certainty in a novel attitude. In Study 4, we seek to further explore dispositional attitude certainty by examining whether it predicts important attitudinally relevant outcomes.…”
Section: Discussionmentioning
confidence: 71%
“…Second, thresholds of different persons probably also vary. For example, persons differ in their disposition to adopt negative or positive attitudes (Eschleman, Bowling, & Judge, 2015; Hepler & Albarracín, 2013). Third, whether one has endorsed (not endorsed) an evaluative reaction in the past will probably also heighten (lower) the threshold of this evaluative reaction in the future, implying that the evaluative reaction is more likely to be endorsed (not endorsed) in the future.…”
Section: The Causal Attitude Network (Can) Modelmentioning
confidence: 99%
“…Some research, however, has suggested that implicit positivity is associated with positive health and well‐being outcomes in the workplace. For example, measures of broad positivity towards neutral objects and situations have been shown to positively relate to both life and job satisfaction (Eschleman, Bowling, & Judge, ). Moreover, assessments of positive mindset using person‐perception approaches have shown that having a positive mindset is associated with higher levels of organisational satisfaction, less cynicism, greater identification with their organisation, and more positive peer ratings of personality and popularity (Wood, Harms, & Vazire, ).…”
Section: Introductionmentioning
confidence: 99%